Implementasi Teknologi Kecerdasan Buatan Dalam Pengembangan Media Pembelajaran Pengenalan Budaya Sasak Gendang Beleq Berbasis Web - Hariman Bahtiar; Rosida; L. M. Samsu (Infotek: Jurnal Informatika dan Teknologi, 2026)
The use of Artificial Intelligence (AI) in developing learning media can enhance the quality of education, make it more engaging, and help preserve cultural heritage such as the Sasak Culture of Gendang Beleq. Based on observations and interviews that were conducted, it was found that 60% of the total 23 students, or about 13 students from class 3B at Sekolah Dasar Negeri 3 Pancor, were not very familiar with Gendang Beleq, such as knowing the names of the musical instruments, the sound characteristics, and the history of Gendang Beleq in the local content subject. Teachers at SDN 3 Pancor still use books as teaching materials for students. The content from the books is usually not interactive, so students can only read the information without interacting, which may make learning feel boring and less engaging for some students. Therefore, this study aimed to address the difficulties students face in recognizing the Sasak Culture of Gendang Beleq at Sekolah Dasar Negeri 3 Pancor by developing web-based interactive learning media that utilizes Artificial Intelligence technology to create videos, images, and audio as tools for teaching and learning activities. This research was carried out through problem analysis, data collection, design phase, development phase, testing, and implementation. The results of the study showed positive feedback, evidenced by the testing of the interactive learning media which did not show any errors and received a success rate of 79%, which falls into the good category. Thus, it can be said that the interactive learning media on the Sasak Culture of Gendang Beleq is suitable for use at SDN 3 Pancor.